2011
DOI: 10.3810/psm.2011.09.1928
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Versus Anatomic Guidance for Intra-articular and Periarticular Injection: A Systematic Review

Abstract: This systematic review can confirm that accuracy is improved with the use of ultrasound-guided intra-articular injection. We can also confirm that short-term outcome improvements are present using ultrasound-guided injection techniques but can confirm no difference in long-term outcome measures using either technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 26 publications
2
41
0
3
Order By: Relevance
“…Although there are few absolute indications for the performance of ultrasound-guided interventional procedures, studies have clearly demonstrated that needle placement is more accurate with image guidance, specifically ultrasound, when compared to anatomical landmark or unguided techniques at a variety of anatomical locations [8][9][10][11][12][13]. The data are conflicting whether this translates into improved clinical efficacy [9,[14][15][16].…”
Section: Indications and Specifications For Ultrasound Guided Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…Although there are few absolute indications for the performance of ultrasound-guided interventional procedures, studies have clearly demonstrated that needle placement is more accurate with image guidance, specifically ultrasound, when compared to anatomical landmark or unguided techniques at a variety of anatomical locations [8][9][10][11][12][13]. The data are conflicting whether this translates into improved clinical efficacy [9,[14][15][16].…”
Section: Indications and Specifications For Ultrasound Guided Proceduresmentioning
confidence: 93%
“…The data are conflicting whether this translates into improved clinical efficacy [9,[14][15][16]. Cost-effectiveness has also become an essential part of the equation when assessing the clinical utility of procedures and tests.…”
Section: Indications and Specifications For Ultrasound Guided Proceduresmentioning
confidence: 99%
“…26 In a systematic review, investigators reported a significant clinical response in a short-term follow-up using US guided injection compared to blind injections regardless of the anatomic site. 13 Considering this discrepancy, a review article that was published in 2013 concluded that more studies are needed to prove the possible priority of US guided injections in clinical efficacy. 20 However, patients in some of these studies were not blinded to the injection technique and this later became the source of criticism of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Even so, the usefulness of ultrasonography (US) in intra-structural injection and its possible effect on improving the clinical outcomes have been assessed in a few studies, and the consequent results have demonstrated significant discrepancy. [9][10][11][12][13] The available data involving hyaloronic acid is even more restricted compared to corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound guidance of intra-articular joint injections (mainly the knee joint) improves needle placement and injection accuracy in comparison with palpation/anatomic landmark techniques, which improves patient-reported clinical outcomes and cost-effectiveness [23,24]. Ultrasoundguided interventional procedures for patients with chronic pelvic pain (e.g., pudendal neuralgia, piriformis syndrome, and "border nerve" syndrome) were also reported [25].…”
Section: Neuraxial and Chronic Pain Proceduresmentioning
confidence: 99%